Allogeneic hematopoietic stem cell transplantation (allo SCT) for chronic myeloid leukemia in the imatinib era: evaluation of its impact within a subgroup of the randomized German CML Study IV - Saußele, Susanne; Lauseker, Michael; Gratwohl, Alois; Beelen, Dietrich W.; Bunjes, Donald; Schwerdtfeger, Rainer; Kolb, Hans-Jochem; Ho, Anthony Dick; Falge, Christiane; Holler, Ernst; Schlimok, Günter; Zander, Axel R.; et al. (Blood, 2010)
The role of allogeneic stem cell transplantation in chronic myeloid leukemia is being reevaluated. Whereas drug treatment has been shown to be superior in first-line treatment, data on allogeneic hematopoietic stem cell transplantation (allo SCT) as second-line therapy after imatinib failure are scarce. Using an interim safety analysis of the randomized German CML Study IV designed to optimize imatinib therapy by combination, dose escalation, and transplantation, we here report on 84 patients who underwent consecutive transplantation according to predefined criteria (low European Group for Blood and Marrow Transplantation [EBMT] score, imatinib failure, and advanced disease). Three-year survival after transplantation of 56 patients in chronic phase was 91% (median follow-up: 30 months). Transplantation-related mortality was 8%. In a matched pair comparison of patients who received a transplant and those who did not, survival was not different. Three-year survival after transplantation of 28 patients in advanced phase was 59%. Eighty-eight percent of patients who received a transplant achieved complete molecular remissions. We conclude that allo SCT could become the preferred second-line option after imatinib failure for suitable patients with a donor. The study is registered at the National Institutes of Health, http://clinicaltrials.gov: NCT00055874.